The Development of System and Content of Capture the Flag (CTF) Platform - Mohd Fadzil, Muhammad Atif (Applied Information Technology And Computer Science, 2025)
New tools and methods have led to a continuous increase in cyber-crime, causing more harm through a rise in attacks. The demand for cybersecurity professionals is exceptionally high due to the increasing frequency and sophistication of cyber-attacks, prompting many universities to offer courses in this field. While the course curriculum is suitable, there’s room for improvement by focusing on hands-on skills through assessments. Hence, a Capture The Flag (CTF) platform has been developed for Bachelor’s in Computer Science (Information Security) with Honours (BIS) students. This platform provides practical challenges related to cybersecurity. BIS students can become familiar with a CTF environment featuring real-life challenges. The Agile methodology was used to develop this platform on the Ubuntu platform, utilizing the CTFd framework for a smooth development process. The platform aims to expose BIS students to CTF scenarios, enhancing their hands-on assessment skills in cybersecurity.